Humanitarian intervention, altruism, and the limits of casuistry. - Miller, Richard B. (Journal of Religious Ethics, 2000)
Argues that the ethics of humanitarian intervention cannot be readily subsumed by the ethics of just war without due attention to matters of political and moral motivation. Use of humanitarian principles to justify military intervention in other countries; Basic features of casuistry; Relationship between casuistry and humanitarian intervention; Difference in motives behind just war and humanitarianism.